Parodie, pastisze i recykling w prozie Stanisława Lema - Gajewska, Agnieszka (My University, 2014)
The article analyzes ways in which Stanislaw Lem’s short stories collected in Sezam i inne opowiadania [Sesame and Other Stories] (first published in 1954) are a parody and satire on the imperialistic policies of both the USA and the Soviet Union. Parody and satire are discussed against a comparative background of specific examples of contemporary Polish and foreign literary works and with reference to the findings of Polish and international literary studies. As a result, the author postulates in the article that new politically subversive meanings of the stories unravel. Another issue considered in the analysis is Lem’s dexterous play with censorship by means of irony and parody (especially by hyperbolizing) thanks to which Polish censorship completely failed to decipher this double-dealing. The author comes to the conclusion that the criticism of imperial politics of the US in Lem’s short stories in question turns out to be a critique of the cold war politics of the Soviet Union as well.
Parody, pastiche and recycling in Stanislaw Lem’s prose
Artykuł dotyczy pierwszego opublikowanego zbioru opowiadań Stanisława Lema, zatytułowanego Sezam z 1954 roku. Szczegółowa interpretacja cyklu skupia się na przedstawieniu strategii pisarskich stosowanych przez Lema, które umożliwiły sparodiowanie prozy produkcyjnej i antyimperialistycznej jeszcze w czasach stalinowskich. Autorka artykułu wskazała przy tym na politycznie wywrotowe znaczenie Sezamu, umieszczając zbiór wśród utworów zapowiadających odwilż. Ponadto w interpretacji opisane zostały środki stylistyczne (m.in. hiperbola) umożliwiające podjęcie gry z cenzurą, która nie dostrzegła w tym pierwszym zbiorze opowiadań ironicznego dystansu. Artykuł dowodzi, że krytyka imperialnej polityki USA w krótkich opowiadaniach Lema stała się jednocześnie krytyką zimnowojennej polityki ZSRR.